(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The article examines mainly two key aspects of Kazakh carpet making traditions: a) typology of certain types of carpets and rugs; b) the semantics of the ornamental composition, as a kind of artistically organized text for reading the “semantic field” of a carpet product. The source base for studying the issue is the collection of carpets and carpet products of the Central State Museum of the Republic of Kazakhstan, collected from almost all regions of the republic. It is concluded that according to the materials used, manufacturing techniques, and practical purpose, these products are typologically divided into the following five groups: 1) pile carpets (“qali kilem”); 2) pileless carpets (“taqyr kilem”, “tyqyr kilem”, occasionally, “taz kilem”); 3) alasha (floor carpet); 4) wall carpets (“tuskilem»); 5) carpets of small forms – saddlebags “qorjyn”; “bogjama” or “ten” (for transportation and storage of small household items, mostly soft goods); “dorba” (bag of various sizes for storage and transport of clothing and bedding, and other commercial and household items in small sizes; “qarshyn”, “kerme”, “shabadan” (soft bags of various sizes); “qap” (bags of various sizes used predominantly for household); “jerjastyq”, pillowcases etc. The author pays special attention to the study of the structural organization of the ornamental space of a traditional carpet. The researcher believes that this aesthetically organized space implements the traditional Kazakh idea of a nomadic lifestyle as an ideal model of social organization. Key words: carpet, pile carpet, lint-free carpet, small-sized carpets, ornament, iconography, composition, semantics.